Public libraries in Norway and the Covid-19 pandemic - Skare, Roswitha (Proceedings from the Document Academy, 2021)
Public libraries have played a central role in natural disasters such as the tornado in the Gulf of Mexico in 2004/2005 and the tsunami in the Tohoku region of Japan in 2011, but also in the financial crisis from 2008. While public libraries in these crises took on a very active role in providing shelter and infrastructure for their citizens, health crises seem to tell a different story. The Covid-19 pandemic that hit Europe and Norway in March 2020 caused a lock-down of public libraries’ buildings for several weeks, as was the case in almost every other European country. This paper investigates the situation for the public library in Tromsø (Norway) in the period from 12 March 2020 and towards a gradual reopening of the library building to the public in April the same year.